Coral reef island shoreline change and the dynamic response of the freshwater lens, Huvadhoo Atoll, Maldives - Carruthers, Lucy; East, Holly; Ersek, Vasile; Suggitt, Andrew; Campbell, Millie; Lee, Kara; Naylor, Victoria; Scurrah, Dominic; Taylor, Liam (Frontiers in Marine Science, 2023)
Low-lying coral reef islands have been projected to become uninhabitable by the end of the century due to sea level rise, but such projections of vulnerability assume that reef islands are static landforms that flood incrementally with sea level rise. In fact, GIS-based reef island shoreline analyses have demonstrated that reef islands are highly dynamic landforms that may adjust their shorelines in response to changing environmental conditions. However, the vast majority of reef island shoreline analyses have been undertaken in the Pacific Ocean, leaving our understanding of changes in the Indian Ocean more limited. Further, our knowledge of how island dynamics can impact groundwater resources is restricted due to the assumption that islands will exhibit purely erosional responses to sea level rise. Here, we analyse shoreline evolution on 49 reef islands over a 50-year timeframe in Huvadhoo Atoll, Maldives. Additionally, rates of shoreline change were used to undertake numerical modelling of shifts in freshwater lens volume in 2030, 2050 and 2100 in response to changes in recharge. Despite sea level rising at 4.24 mm/year (1969-2019), accretion was prevalent on 53% of islands, with the remaining islands eroding (25%) or remaining stable (22%). Average net shoreline movement was 4.13 m, ranging from -17.51 to 65.73 m; and the average rate of shoreline change (weighted linear regression) was 0.13 m/year, ranging from -0.07 to 2.65 m/year. The magnitudes and rates of reef island evolution were found to be highly site-specific, with island type found to be the only significant predictor of either net shoreline movement or weighted linear regression. Results suggest that freshwater lens volume was substantially impacted by shoreline change compared to changes in recharge whereby accretion and erosion led to large increases (up to 65.05%) decreases (up to -50.4%) in les volume, respectively. We suggest that the capacity of reef islands to both (1) adjust their shorelines, and even accrete, under conditions of sea level rise; and (2) increase their storage of groundwater over the coming decades represents highly valuable geomorphic ecosystem services.